The Harm Principle as a Basis for the Criminalization of Match Fixing in Football Competitions - Emmilia Rusdiana; Abdul Madjid; Milda Istiqomah (Faculty of Law, Universitas Lampung, 2025)
The credibility of football has been repeatedly questioned due to allegations of bribery and related violations, as reflected in judicial decisions such as Case No. 51/Pid.Sus/2019/PN.Bnr, which established bribery as the initial act in match fixing. This study, employing normative legal research with legislative and conceptual approaches and analyzed through philosophical interpretation, examines match fixing through the principle of loss as the basis for its criminalization. The findings show that bribery constitutes a mala in se offense, inherently wrongful in nature, and that the principle of loss satisfies the indicators of criminalization by recognizing both material and immaterial harm to society. These results confirm that bribery, with identifiable victims in the community, underlies the complexity of match fixing and provide new insights to raise public awareness..